Modelo de dois dubletos de higgs - Silva, Paulo José Ferreira Porfírio da (2013)
In this dissertation we did a complete review of the StandardModel(SM), emphasizing the weak interactions, this in order to treat an extension of theMP with addition of a doublet of scalar theory, known in the literature asModel with Two Higgs doublets (2HDM). We will treat this model from the point of view of both aspects: when two doublets develop the expected value of the vacuum(vev) and when only one develops doublets vev, utilize the potential of 2HDM does not violate CP. These two models are particularly important because they are quite simple and can solve some problems that are open in Physics, one of the most important is the dark matter (DM). Furthermore, we will use the formalism of oblique parameters, radiative corrections involving first order, to parameterize the effects of New Physics (NP). We will present the phenomenology to obtain 2HDMI and regions that are in agreement with the experimental data.